O avesso da(s) identidade(s) “homoerótica(s)” masculinas nos espaços homofóbicos na terra dos marechais (Maceió-AL): lugares e não-lugares - Silva, Flavio Santos da (2009)
In this work we analyze hidden identities of male homoerotic in Maceió-AL. (HALL, 1998; CANCLINI, 2005; FREIRE, 1995; TREVISAN, 2004; GREEN, 2000; FIGARI, 2007; FRY & MACRAE, 1991; GUIMARÃES, 2004; FARIAS & RISCADO, 2002). To comprehend these identities, we use concepts such as violence and space (place and non-place). This research consisted of observation of some particular places called “espaços de pegação” and “espaços de cassação”, questionnaire, interviews and information from Secretaria de Defesa Social de Alagoas. In doing so, we searched for understand how these male homoerotic defines themselves, how they deal with their identities in spaces (places and non-places) and which would be the impacts of violence in their life, considering the social imaginary and dominant cultural codes and heterosexual conventional relational models. Many of them demonstrate, in interviews, that they do not desire to assume a gay identity, accepting, in certain way, social dominant codes. For them, homoerotic attitudes live with family constitution wishes. Intolerants attitudes by conservatives sectors of the city are perceived for the majority characters research as inhibiting of a possible visibility. On the other hand, homophobic attitudes evidenced by higher levels of symbolical and physics violence; produce certain vulnerability to male homoerotic. Besides, we verified that some tensions suffered by them represents permanent fear and insecurity, but this feelings does not move them away from homoerotic attitude, in fact, it makes they modify its strategies in order to keep hidden and to materialize its desires.